2020
DOI: 10.1186/s13014-020-01567-7
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of recurrence in anal cancer: a detailed analysis

Abstract: Background: Anal cancer is a rare disease, which might be the reason for the "one size fits all" approach still used for radiotherapy target contouring. To refine and individualize future guidelines, detailed and contemporary pattern of recurrence studies are needed. Methods: Consecutive anal cancer patients, all treated with curative intent intensity-modulated radiotherapy (IMRT), were retrospectively studied (n = 170). Data was extracted from medical records and radiological images. Radiotherapy planning CT'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
1
18
1
Order By: Relevance
“…With a median follow-up of 50 months (range 14À117 months), the number of events were: LR (n ¼ 20), DR (n ¼ 34), OS (n ¼ 36), ACSS (n ¼ 23), and NACD (n ¼ 13). As previously reported, 5-year OS and ACSS were 79.9% and 86.1%, respectively [14].…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…With a median follow-up of 50 months (range 14À117 months), the number of events were: LR (n ¼ 20), DR (n ¼ 34), OS (n ¼ 36), ACSS (n ¼ 23), and NACD (n ¼ 13). As previously reported, 5-year OS and ACSS were 79.9% and 86.1%, respectively [14].…”
Section: Resultssupporting
confidence: 82%
“…The study population has been described previously [14]. Briefly, consecutive patients with non-metastatic squamous cell carcinoma of the anus (anal cancer), who received intensity-modulated radiotherapy (IMRT) with curative intent at Skåne University Hospital, Sweden, during the time period August 2009-December 2017 were included (n ¼ 170).…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially in locally advanced tumors, the cure rates remain suboptimal and locoregional recurrences are a frequent site of failure [ 3 , 4 ]. Additionally, distant metastases occur in about 20% of patients during follow-up [ 6 ]. Radiotherapy delivery with IMRT leads to a reduction in CRT-related toxicities, to better treatment compliance, and to better oncologic outcomes [ 11 , 14 , 17 , 18 , 19 , 20 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In locally advanced tumors (T3–4/N+), survival rates of about 60% require further improvements [ 3 , 4 ]. Recent studies have reported that locoregional recurrences are a major site of failure [ 5 , 6 ]. At the same time, definitive CRT is associated with high rates of acute and hematologic toxicities [ 7 ].…”
Section: Introductionmentioning
confidence: 99%